Serving King and Sultan: Pavao Grgurić and his role on the Hungaro-Ottoman frontier in southern Bosnia, c. 1463-77 - Ursinus, Michael (Life on the Ottoman border, 2022)
Pavao Grgurić, a Christian ‘man of the sword’ active during the transition period between the last years of the independent Bosnian kingdom and the beginning of Ottoman rule, was an influential office holder in the Livno and (later) Neretva regions who remained a Christian for his entire (visible) career. Being initially awarded as his timar a compact group of 14 villages (clearly a feudal complex) in the immediate vicinity of Hum fortress (near Podhum village south of Livno) which he was to guard, he was later given an aggregate timar worth at least three times that of a dizdar or fortress commander. This poses the question of his exact function and standing within the Bosnian dual regime during the period of early Ottoman rule in the province. Rather than being enslaved later by the enemy, he appears to have been arrested on demand of the Sultan himself. His career can be traced for the period between 1463 and 1477.